2001
DOI: 10.1038/84839
|View full text |Cite
|
Sign up to set email alerts
|

Localized Igf-1 transgene expression sustains hypertrophy and regeneration in senescent skeletal muscle

Abstract: Aging skeletal muscles suffer a steady decline in mass and functional performance, and compromised muscle integrity as fibrotic invasions replace contractile tissue, accompanied by a characteristic loss in the fastest, most powerful muscle fibers. The same programmed deficits in muscle structure and function are found in numerous neurodegenerative syndromes and disease-related cachexia. We have generated a model of persistent, functional myocyte hypertrophy using a tissue-restricted transgene encoding a locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
858
11
15

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 976 publications
(932 citation statements)
references
References 26 publications
48
858
11
15
Order By: Relevance
“…In agreement with previous reports suggesting that insulin/IGF-1 promotes proliferation, we observed 5-bromo-2-deoxyuridine incorporation into mononucleated reserve cells upon treatment of differentiated C2 cells with insulin or insulin and LiCl (unpublished observations). In vivo, the hypertrophic effect of IGF-1 alone on skeletal muscles in mice is well documented (Barton-Davis et al, 1998;Musaro et al, 2001). A similar effect was shown on myotube hypertrophy ex vivo (Rommel et al, 2001).…”
Section: Wnt and Insulin Signaling Pathways Have Synergistic Effects mentioning
confidence: 50%
“…In agreement with previous reports suggesting that insulin/IGF-1 promotes proliferation, we observed 5-bromo-2-deoxyuridine incorporation into mononucleated reserve cells upon treatment of differentiated C2 cells with insulin or insulin and LiCl (unpublished observations). In vivo, the hypertrophic effect of IGF-1 alone on skeletal muscles in mice is well documented (Barton-Davis et al, 1998;Musaro et al, 2001). A similar effect was shown on myotube hypertrophy ex vivo (Rommel et al, 2001).…”
Section: Wnt and Insulin Signaling Pathways Have Synergistic Effects mentioning
confidence: 50%
“…Therefore, protection of relative muscle mass and muscle morphology against age-induced changes in the wheel running group may be in part a function of partial protection against reduced IGF-1 protein with aging. Although the intermediate mechanisms for IGF-1 protection against age-induced sarcopenia remain uncertain, previous aging studies indicate that IGF-1 could protect muscle mass and morphology via increased protein synthesis, muscle regeneration, increased number of dihydropyridine sensitive voltage-dependent Ca 2+ channels (DHPRs), and increased protection against cell necrosis and apoptosis of myonuclei and satellite cells (Musaro et al, 2001;Siu et al, 2004Siu et al, , 2005Song et al, 2005;Winn et al, 2002). For example, IGF-1 stimulation by lifelong exercise could protect against muscle fiber atrophy and stimulate cell growth through a cascade involving Akt phosphorylation and downstream elevation of mTOR, NF-κB (nuclear factor-kappaB), and heat shock proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Such properties of IGF-1 have been shown to be beneficial to ageing, atrophic, and dystrophic muscles (Barton-Davis et al, 1998;Lynch et al, 2001;Musarò et al, 2001). IGF-1 has the additional effect of converting fibres to a fast glycolytic phenotype, as evident by raised expression of glycolytic enzymes in IGF-1-transfected C2C12 myotubes (Semsarian et al, 1999), by modest rise in fast 2b fibres in transgenic mice carrying muscle IGF-1 isoform driven by a rat myosin light chain (MLC)-1/3 promoter (Musarò et al, 2001) and by raised type 2a and 2b fibres at the expense of slow fibres in IGF-1-treated dystrophic mice (Lynch et al, 2001). As previously indicated, clenbuterol (a b 2 -agonist) treated rats (Ryall et al, 2002) as well as myostatin-null mice (Steelman et al, 2006) not only showed muscle hypertrophy but also slow-to-fast fibre conversion.…”
Section: Fibre Types: Coordinated Isoform-specific Expressionmentioning
confidence: 99%